Validation of a field test to determine the maximal aerobic power in triathletes and endurance cyclists. Issue 3 (18th December 2006) - González-Haro, C; Galilea, P A; Drobnic, F; Escanero, J F
Abstract : Objective: To validate a field test to assess the maximal and submaximal exercise aerobic adaptation under specific conditions, for endurance modality cyclists and triathletes. Methods: 30 male and 4 female endurance modality cyclists and triathletes, with heterogeneous performance levels, performed three incremental tests: one in the laboratory and two in the field. Assessment of the validity of the field protocol was carried out by the Student's t test, intraclass correlation coefficient (ICC) and coefficient of variation (CV) of the maximal variables (maximal aerobic speed (MAS), maximal aerobic power (MAP), maximal heart rate (HRmax ), maximal blood lactate concentration ([La − ]max ) and maximal oxygen uptake (VO2max )) and submaximal variables (heart rate, HR) measured in each one of the tests. The errors in measurement were calculated. The repeatability of the field tests was assessed by means of the test–retest of the two field tests, and the validity by means of the test–retest of the laboratory test with respect to the mean of the two field tests. Results: No significant differences were found between the two field tests for any of the variables studied, but differences did exist for some variables between the laboratory tests with respect to the field tests (MAP, [La − ]max, humidity (H), barometric pressure (Pb) and some characteristics of the protocols). The ICC of all the variables was high and the CV for the MAP was small. Furthermore, the measurement errors were small and therefore, assumable. Conclusions: The incremental protocol of the proposed field test turned out to be valid to assess the maximal and submaximal aerobic adaptation.